Perilaku Komunikasi Verbal dan Nonverbal Orang Tua dengan Remaja Pengguna Gadget Aktif: Kasus Tiga Keluarga di Gang Rukun Sidoarjo Hilir Kecamatan Tembung - Salam, Rudi; Ritonga, Irham; Sikumbang, Ahmad Tamrin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In everyday life, communication is not just about transmitting messages; it involves complex verbal and nonverbal dimensions. The digital era, driven by the advancement of Information and Communication Technology (ICT), has brought significant changes in the way we interact. Its influence is strongly felt among teenagers who are actively involved in using gadgets. Although designed to facilitate communication, gadgets often become a potential source of problems in human interaction. This research uses a qualitative method with descriptive data analysis, focusing on the communication dynamics between parents and teenagers who actively use gadgets. The research results show that the use of the Batak language in verbal communication by parents is the main highlight, highlighting the cultural richness in family interaction. In addition to the verbal dimension, interaction is also observed through nonverbal communication including facial expressions, body movements, and body posture in the context of parent-teenager relationships.